An Introduction to SARS Coronavirus 2; Comparative Analysis with MERS and SARS Coronaviruses: A Brief Review - Mahsa TAHERIZADEH; Alireza TABIBZADEH; Mahshid PANAHI; Fahimeh SAFARNEZHAD TAMESHKEL; Mahsa GOLAHDOOZ; Mohammad Hadi KARBALAIE NIYA (Tehran University of Medical Sciences, 2020)
Since the 1970 the replication and pathogenesis mechanism of different coronaviruses have been studded.. In 2002-2003, SARS (Severe Acute Respiratory Syndrome coronavirus) in China emerged which resulted in 8098 cases and 774 deaths. About 10 years later in 2012, the MERS (Middle East Respiratory Syndrome coronavirus) spread in Middle Eastern countries and leads to infection in 2465 cases. In Dec 2019, another acute respiratory disease caused by a novel coronavirus named SARS-2 emerged in Wuhan, China. The virus is assumed to be mainly transmitted by respiratory droplets. Travels and communications leads to high prevalence of COVID-19 (Coronavirus Disease 2019) in the world, and currently in Iran. The current review was conducted to compare the virus structure, genome organization, virus life cycle, pathogenesis and prediction the future of COVID-19.